Współczesna proza Ziemi Lubuskiej - regionalne małe ojczyzny i muzealizacja pamięci = Contemporary prose of Lubusz Land - little regional motherlands and musealization of memory - Gieba, Kamila (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article concerns Lubusz Land's contemporary prose: novels written by Krzysztof Fedorowicz ("Grünberg"), Maria Sidorska-Ryczkowska ("Stacyjka na wschodzie i zachodzie" and "Klucze do rzeki"), Edward Derylak ("Wedelmann"). The authoress analyses these narrations on the background of little homelands prose. The article is also an attempt to determine the regional features of the works about Lubusz Land.
Keywords: małe ojczyzny; Ziemia Lubuska; literatura regionalna; przesiedlenia; literatura - 21 w.; motherlands; Lubusz Land; regional literature; resettlements; literature - the 21st century